Наїзди та грабежі в шляхетському соціумі Волині (1566 р. — початок ХVII ст.) - Старченко, Н. (Україна в Центрально-Східній Європі, 2013)
У статті аналізується побутування в ранньомодерному шляхетському соціумі Волині найпоширеніших правопорушень — наїздів та грабежів, які у межах шляхетської культури ворожості були символічним актом оголошення про помсту, обов’язковим для почтивого шляхтича в боротьбі з недругами, специфічною формою порахунків за уразу для честі, елементами двобою поміж супротивниками за добру славу у спільноті, особливим лицарським правом, за допомогою якого відновлювалася справедливість. В статье анализируется бытование в шляхетском социуме Волыни раннего нового времени наиболее распространенных правонарушений — наездов и грабежей,которые в пределах шляхетской культуры вражды были символическим актом объявления о мести, обязательны для почтивого шляхтича в борьбе с неприятелями, специфической формой расчетов за оскорбление чести, элементами поединка между противниками за добрую славу в сообществе, особенным рыцарским правом, с помощью которого восстанавливалась справедливость. In the present article, I have analyzed assaults and robberies, the two most common crimes in the early modern Volhynian gentry community. While committing such acts was to be strictly punished according to laws, they nonetheless served an important function in the gentry culture of hostility, where honour and the gentrymen’s good reputation were the main regulators of behaviour. They served as symbolic declarations of revenge, mandatory for the honourable gentrymen, a compulsory step in fights against enemies, a part of a duel for reputation within the community, a specific knightly law that helped to restore justice. Therefore, the crimes for committing which a gentryman could lose his life and honour were in fact tolerated by the community. However, these crimes were carried out in a relatively mild manner regulated by the rules that everybody knew, and, had a gentryman decided to break them, it could cost him his honour and prestige.